2022
DOI: 10.3389/fphar.2022.750554
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of TSPO Modulators on Electroencephalogram Activity and Exploratory Behavior

Abstract: Network communication in the CNS relies upon multiple neuronal and glial signaling pathways. In addition to synaptic transmission, other organelles such as mitochondria play roles in cellular signaling. One highly conserved mitochondrial signaling mechanism involves the 18 kDa translocator protein (TSPO) of the outer mitochondrial membrane. Originally, TSPO was identified as a binding site for benzodiazepines in the periphery. It was later discovered that TSPO is found in mitochondria, including in CNS cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Second, the dose of XBD173 (5 mg/kg) used by Shi et al, [ 26 ], as well as the duration (consecutive days), varies considerably from our study (1 mg/kg every alternate day). In line with these hypotheses, a recent study showed that XBD173 at a higher dosage (5 mg/kg) compared to the lower dosage (1 mg/kg) affects the mouse locomotory and exploratory behavior and also decreases the gamma power in EEG recordings [ 27 ]. Given the importance of gamma power in maintaining working memory-related processes, one could speculate that a decrease in gamma power resulting from a higher dosage of XBD173 impairs cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the dose of XBD173 (5 mg/kg) used by Shi et al, [ 26 ], as well as the duration (consecutive days), varies considerably from our study (1 mg/kg every alternate day). In line with these hypotheses, a recent study showed that XBD173 at a higher dosage (5 mg/kg) compared to the lower dosage (1 mg/kg) affects the mouse locomotory and exploratory behavior and also decreases the gamma power in EEG recordings [ 27 ]. Given the importance of gamma power in maintaining working memory-related processes, one could speculate that a decrease in gamma power resulting from a higher dosage of XBD173 impairs cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent findings from Shi et al, suggest that diazepam via TSPO alters synaptic plasticity [ 26 ]. Additionally, both the ligands Ro5-4864 and PK11195 have been shown to alter the locomotor and exploratory behavior as well as affect band-specific changes in EEG [ 27 ]. As such, it remains to be resolved whether TSPO ligands exert beneficial or detrimental effects on neuroplasticity.…”
Section: Introductionmentioning
confidence: 99%